2018
DOI: 10.1080/09638288.2018.1492031
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing participation in physical activity after dysvascular amputation: a qualitative meta-synthesis

Abstract: Confirm psychosocial targets of physical activity behavior change intervention after dysvascular LLA using quantitative methods.• Develop and test a physical activity behavior change intervention tailored to the needs of people with dysvascular LLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…For example, a qualitative metasynthesis identified patient education, motivation, social support, self-efficacy, and prosthesis factors as overarching categories influencing physical activity for people with LLA. 65 In addition, higher age, less experience with the prosthesis, more comorbidities, and lower functional capacity are associated with lower levels of physical activity after LLA. 63,66 Also, U.S. military veterans have slightly higher physical activity than nonveterans, although veterans who use the Veterans Health Administration for health care may have slightly less physical activity than other veterans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a qualitative metasynthesis identified patient education, motivation, social support, self-efficacy, and prosthesis factors as overarching categories influencing physical activity for people with LLA. 65 In addition, higher age, less experience with the prosthesis, more comorbidities, and lower functional capacity are associated with lower levels of physical activity after LLA. 63,66 Also, U.S. military veterans have slightly higher physical activity than nonveterans, although veterans who use the Veterans Health Administration for health care may have slightly less physical activity than other veterans.…”
Section: Discussionmentioning
confidence: 99%
“…There are significant barriers to participation in the years following LLA given limited education and access to timely rehabilitation and prosthetic services, mobility challenges, difficulties accessing the physical environment and public transport, public attitudes to disability, poor mental health, social isolation and loss of roles within family and society that define a person and bring meaning and purpose to life. [3][4][5][6] Our understanding of the impact of these factors on work participation is limited, given that most studies have used quantitative methods to examine the effects of demographic and amputation-related factors on work participation after LLA in countries with well-developed healthcare systems. [7][8][9][10] Few studies have examined the effects of pain, level of mobility or the effect of comorbidities, 11,12 or described the impact of the environmental or psychosocial factors on work participation following LLA.…”
Section: Introductionmentioning
confidence: 99%
“…14,41,42 This is not unexpected due to the barriers to PA that this population faces, and is also consistent with previously published literature regarding PA in patients with an amputation. [21][22][23][24][29][30][31]36 The finding that female gender, increasing age, and disease burden correlate with decreased PA is also observed in the general population. 41 In addition, a prior study indicated that female patients are less likely to be successfully fitted with a lower-limb prosthesis than male patients, which could contribute to this disparity.…”
Section: Discussionmentioning
confidence: 68%
“…29 Individuals with an amputation may face challenges to exercise such as lack of accessible equipment and facilities, skin issues on the residual limb, and changes in body image. 23 Additional educational and motivational support may be needed to help initiate PA. 30 Individuals who were active prior to amputation may need to adapt their exercise and find locations where adaptive sports and exercise are possible. 31,32 These difficulties play a role in the decreased participation in sporting events observed in previously active individuals following an amputation.…”
Section: Introductionmentioning
confidence: 99%